2013
DOI: 10.1017/s0022215113000418
|View full text |Cite
|
Sign up to set email alerts
|

The management of recurrent croup in children

Abstract: Airway anomalies are common in children that present with recurrent croup. Laryngobronchoscopy allows identification of the cause of croup and enables a more accurate prognosis. In the current study, laryngobronchoscopy findings that indicated reflux were predictive of benefit from anti-reflux medications, whereas the clinical presentation of reflux was not. Routine measurement of immunoglobulin E and complement proteins did not appear to be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 20 publications
0
34
0
5
Order By: Relevance
“…Previous studies have demonstrated the high prevalence of GERD between 47% and 100% in children with recurrent croup. A study by Rankin et al . revealed that 91% of children with findings suggestive of GERD on bronchoscopy had a decreased severity and frequency of croup episodes after treatment with antireflux medication for a median period of 9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the high prevalence of GERD between 47% and 100% in children with recurrent croup. A study by Rankin et al . revealed that 91% of children with findings suggestive of GERD on bronchoscopy had a decreased severity and frequency of croup episodes after treatment with antireflux medication for a median period of 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…In four children who underwent a repeat bronchoscopy after treatment with antireflux medication, 100% had a reduction in the severity of their subglottic stenosis. Given that the correlation between symptoms and objective evidence of GERD is poor, and the evidence that antireflux treatment may be effective in this population, a trial of antireflux treatment should be considered even in children who do not report reflux symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies on recurrent croup and allergy showed that children with specific parainfluenza IgE antibodies who had croup more frequently released histamine into the airway than children with upper respiratory tract infection caused by the same pathogen [23,24]. The possible correlation between allergy and croup was investigated over the years, and this may have resulted in the usage of antihistaminics in treatment of croup [25][26][27][28]. Since treatment with antihistaminics did not bring any significant improvement, it was abandoned, which can also be seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant decrease in antihistaminic use by otolaryngologists (from 67.7% in 1993 to 0.0% in 2013) and paediatricians as well (from 43.2% in 1993 to 2.0% in 2013). Although there was a clear link between atopy and recurrent laryngitis, one of the recent studies which tried to connect recurrent croup and allergy showed that positive RAST did not correlate with clinical symptoms [23,[25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have in turn ascribed cases of recurrent croup, laryngomalacia and subglottic stenosis in infants (Contencin and Narcy, 1992;Kwong et al, 2007;Rankin et al, 2013;Ulualp et al, 2007b;2007a) as well as apneas-bradycardias in newborns (Vermeylen et al, 2005) to reflux laryngitis. Such causative link may stem from alterations in pharyngolaryngeal reflexes secondary to reflux laryngitis, as reported in adult humans, suggesting a blunted protection against laryngeal penetration and tracheal aspiration (Ulualp et al, 1998).…”
Section: Introductionmentioning
confidence: 99%